2022
DOI: 10.1111/pce.14434
|View full text |Cite
|
Sign up to set email alerts
|

Auxin plays a role in the adaptation of rice to anaerobic germination and seedling establishment

Abstract: Auxin is well known to stimulate coleoptile elongation and rapid seedling growth in the air.However, its role in regulating rice germination and seedling establishment under submergence is largely unknown. Previous studies have shown that excessive levels of IAA frequently cause the inhibition of plant growth and development. In the present study, the high-level accumulation of endogenous IAA is observed under submergence in the dark, stimulating rice coleoptile elongation but limiting the root and primary lea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Another related study showed that nanopriming of O. sativa seeds with the 375 nm CS/TPP NPs (50 μg/mL) resulted in increased germination percentage and seedling vigour index in 7-day-old seedlings in normal growth conditions and under salt stress ( Soni et al, 2023 ). It has been inferred that adsorption of chitosan NPs onto seeds could initiate the biosynthesis of auxin, which stimulates coleoptile elongation ( Lee et al, 2022 ). Furthermore, Hameed et al (2020) reported that treatment of O. sativa seeds with Zn NPs-stabilized chitosan-polyvinyl alcohol (0.16%) elicited the biosynthesis of proteins and upregulated the activities of protease and α-amylase enzymes in comparison with the unprimed seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Another related study showed that nanopriming of O. sativa seeds with the 375 nm CS/TPP NPs (50 μg/mL) resulted in increased germination percentage and seedling vigour index in 7-day-old seedlings in normal growth conditions and under salt stress ( Soni et al, 2023 ). It has been inferred that adsorption of chitosan NPs onto seeds could initiate the biosynthesis of auxin, which stimulates coleoptile elongation ( Lee et al, 2022 ). Furthermore, Hameed et al (2020) reported that treatment of O. sativa seeds with Zn NPs-stabilized chitosan-polyvinyl alcohol (0.16%) elicited the biosynthesis of proteins and upregulated the activities of protease and α-amylase enzymes in comparison with the unprimed seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Submergence downregulates the expression of miR393, thus activating the auxin signaling pathway and stimulating coleoptile elongation in rice [40]. Interestingly, a recent report has shown that a certain threshold level of endogenous auxin is required for rice germination and early seedling growth during submergence [41]. Lee and his co-workers showed that a submergence-repressed miR167 is involved in the metabolic regulation of IAA through the miR167a-ARF-GH3 pathway [41].…”
Section: Hormone Signaling In Ag/agd Regulationmentioning
confidence: 99%
“…Interestingly, a recent report has shown that a certain threshold level of endogenous auxin is required for rice germination and early seedling growth during submergence [41]. Lee and his co-workers showed that a submergence-repressed miR167 is involved in the metabolic regulation of IAA through the miR167a-ARF-GH3 pathway [41]. MiR167-directed ARF mRNA cleavage is accompanied by the downregulation of glycoside hydrolase 3 (GH3) [42].…”
Section: Hormone Signaling In Ag/agd Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This review should facilitate the manipulation of key genes for better performance under flood conditions in rice. Lee et al (2022) reported that auxin is also necessary for rice to adapt to anaerobic germination and seedling establishment; they showed that reduced endogenous IAA enhances rice anaerobic germination tolerance and promotes seedling establishment in rice while excessive accumulation of IAA leads to poor seed germination and seedling establishment, suggesting that there is a certain threshold value for auxin to function in anaerobic germination and seedling establishment (Lee et al, 2022).…”
Section: Abiotic Resilience Of Ricementioning
confidence: 99%